Bromelain and papain from organic residues of Ananas comosus and Carica papaya - Casas Muñoz, Jennifer Janice (2022)
In Peru there are no minimization proposals for the large amount of organic waste discarded daily by economic activities such as in the case of the El Tambo food market. In the present work we use Ananas comosus and Carica papaya peels and seeds to obtain the enzymes bromelain and papain, using the protocol [1] with the following steps: obtaining the juice, enzymatic extraction with ethanol and NaCl, protein concentration and finally the enzymatic activity test is performed by coagulation. From 1 kilogram of residues, 0.3851g with ethanol and 2.123g with NaCl of lyophilized bromelain and 0.3172g with ethanol and 1.0032g with NaCl of lyophilized papain were obtained; it was observed that the treatments with NaCl allowed obtaining a greater amount of product. The tests showed that it is possible to obtain the enzymes from the peels of Ananas comosus and Carica papaya, which poses a possible alternative for the reuse of these residues as nutritional complements for food.